2022
DOI: 10.3390/foods11233903
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coconut Clusters Based on Occlusion Condition Using Attention-Guided Faster R-CNN for Robotic Harvesting

Abstract: Manual harvesting of coconuts is a highly risky and skill-demanding operation, and the population of people involved in coconut tree climbing has been steadily decreasing. Hence, with the evolution of tree-climbing robots and robotic end-effectors, the development of autonomous coconut harvesters with the help of machine vision technologies is of great interest to farmers. However, coconuts are very hard and experience high occlusions on the tree. Hence, accurate detection of coconut clusters based on their oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In addition, a certain degree of occlusion in other fruits also affects label generation accuracy. In a recent study, we noticed some work [ 49 , 50 ] to improve detection performance by setting up attention mechanisms in the model for the fruit occlusion problem. We plan to subsequently analyze this idea and to conduct further research to improve the effectiveness of fruit auto labeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a certain degree of occlusion in other fruits also affects label generation accuracy. In a recent study, we noticed some work [ 49 , 50 ] to improve detection performance by setting up attention mechanisms in the model for the fruit occlusion problem. We plan to subsequently analyze this idea and to conduct further research to improve the effectiveness of fruit auto labeling.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the study, the Yolov5 algorithm was found to be more successful and the Yolov5 algorithm was recommended for walnut detection. Divyanth et al [10] obtained images under different light and at different angles for coconut detection. By performing augmentation on the obtained data, 900 image data were obtained.…”
Section: Related Workmentioning
confidence: 99%
“…Machine vision-based technique is another tool that has demonstrated the potential to replace several manual (visual) methods of grain grade/quality inspection (Jayas & Singh, 2012;Vithu & Moses, 2016). Color imaging systems are machine vision tools that can evaluate sample characteristics according to their visual appearance on the exterior surface (Divyanth et al, 2022a(Divyanth et al, , 2022bHosainpour et al, 2022;Olakanmi et al, 2023;Kheiralipour et al, 2022;Sabzi et al, 2022). Some of their applications include the identification of dockage and foreign material (Paliwal et al, 2003), insect presence (Ridgway et al, 2002), insect infestation (Ebrahimi et al, 2014), microbial infection (Qiu et al, 2019), seed germination , broken kernels (Luo et al, 1999), as well as detection of grain grade/class/type according to kernel size, shape, color, or texture (Majumdar & Jayas, 2000a, 2000b, 2000c, 2000dSabanci et al, 2017).…”
Section: Modernizing Grain Quality Measurement: An Investigation Of T...mentioning
confidence: 99%